EFEKTIVITAS DISIPLIN PEGAWAI TERHADAP PENERAPAN MESIN ABSENSI SIDIK JARI DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BALIKPAPAN - Hasbullah Helmi; Hartutiningsih .; Achmad Djumlani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The aim of research is to describe and analyze the effectiveness of Employee Discipline Towards Automatic Fingerprint Machine. The focus of this research are: timeliness, adherence to the rules, responsibility and reliability of automatic fingerprint machine. Sources of data taken from the informant and key informants. As the informant was civil servants and non-civil servants, while a key informant was the Head of Department. Analysis of the data that is used in this research is the model developed Interactive of Miles and Huberman.